PENGARUH KEPUTUSAN PENDANAAN, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGES PERIODE 2017-2021 - Lukmana, Anggara Soekowati; Widyarti, Endang Tri (Diponegoro Journal of Management, 2023)
ABSTRACT This research is meant to examine the influence of financial performance (funding decision, profability, and dividend policy) to the firm value. Research about firm value need to be done because stock market is one of the sources of firm capital, and one of the economic supports, so from the side of management must take decisions that can maximize firm value, and from the side of investor must know what factors that should be noticed to buy firm stock to get the optimum firm value. This research method uses a quantitative approach with secondary data to be analyzed taken from the financial report data of Food and Beverage companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population in this study were manufacturing companies in the Food and Beverage sub-sector which were listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period, around 30 companies. Using a purposive sampling technique, a sample of 15 companies was obtained. The analysis technique used is multiple linear regression. The results showed that funding decision variables as measured by the Debt to Equity Ratio, profitability as measured by Return on Assets, and dividend policy as measured by the Dividend Payout Ratio had a significant positive effect on firm value as measured by Price to Book Value in Food and Beverages companies Period 2017-2021.